2014
DOI: 10.1128/jcm.01852-13
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a Commercial PCR Assay and a Clinical Prediction Rule for Detection of Toxigenic Clostridium difficile in Asymptomatic Carriers

Abstract: A commercial PCR assay of perirectal swab specimens detected 17 (68%) of 25 asymptomatic carriers of toxigenic Clostridium difficile, including 93% with skin and/or environmental contamination. A clinical prediction rule, followed by PCR screening, could be used to identify carriers at high risk of C. difficile shedding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Additionally, the number of previous hospital stays within the past 6 months raised the probability of a positive CD-PCR by factor 1.6 each (95% CI: 1.1–2.2). This corresponds to previous studies which also determined previous episodes of CDI and treatment with antibiotics as the highest risk factors for a toxigenic CD colonization [34, 35]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, the number of previous hospital stays within the past 6 months raised the probability of a positive CD-PCR by factor 1.6 each (95% CI: 1.1–2.2). This corresponds to previous studies which also determined previous episodes of CDI and treatment with antibiotics as the highest risk factors for a toxigenic CD colonization [34, 35]. …”
Section: Discussionsupporting
confidence: 89%
“…Using PCR from stool samples, as in our study, achieves a timely detection of C.difficile carriers. It has already been shown that rectal swabs taken at admission and tested using PCR following a selective broth preamplification can be used for even faster diagnostic [34, 40]. A disadvantage of the PCR screening test, however, is its relatively high price.…”
Section: Discussionmentioning
confidence: 99%
“…9 Not only do antibiotic-induced disruptions lead to a loss of colonization resistance to MDROs, but once colonization does occur, further disruptions can lead to dominance (defined as a single MDRO constituting ≥30% of the microbiota), which is associated with the occurrence of invasive infection and increased transmission risk through skin and environmental contamination. 10,11 MDROs, such as Clostridium difficile, vancomycin-resistant enterococci (VRE), and carbapenem-resistant Enterobacteriaceae (CRE), are major public health concerns in healthcare settings, where they are transmitted between patients and can colonize the lower intestine in more individuals than they infect. 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…16 Recent advances in diagnostic testing for C. difficile have encouraged the evaluation of the feasibility of screening patients at admission for C. difficile and subsequent application of isolation precautions. [17][18][19] An outcome model identified C. difficile screening, coupled with isolation precautions, as a cost-effective intervention when the proportion of admitted patients with C. difficile colonization was greater than approximately 10%. 20 For healthcare-associated infections, computational models of pathogen transmission have become valuable tools to evaluate healthcare interventions, especially in the absence of controlled intervention studies.…”
mentioning
confidence: 99%